Bond between textile reinforced mortar (TRM) and concrete substrate - Raoof, Saad Mahmood (2017)
There is a growing interest for strengthening and upgrading existing concrete structures both in seismic and non-seismic regions due to their continuous deterioration as a result of aging, degradation induced environment conditions, inadequate maintenance, and the need to meet the modern codes (i.e. Eurocodes). Almost a decade ago, an innovative cement-based composite material, the so-called textile-reinforced mortar (TRM), was introduced in the field of structural retrofitting. TRM comprises high-strength fibres in form of textiles embedded into inorganic matrices such as cement-based mortars. TRM offers well-established advantages such as: fire resistance, low cost, air permeability, and ability to apply on wet surfaces and at ambient of low temperatures. It is well known that the effectiveness of any external strengthening system in increasing the flexural capacity of concrete members depends primarily on the bond between the strengthening material and member’s substrate. This PhD Thesis provides a comprehensive experimental study on the bond behaviour between TRM and concrete substrate and also provides a fundamental understanding of the flexural behaviour of RC beams strengthened with TRM. Firstly, the tensile properties of the textile reinforcement were determined through carrying out tensile tests on bare textiles, and TRM coupons. Secondly, the bond behaviour between TRM and concrete substrates both at ambient and, for the first time, at high temperature was extensively investigated. A total of 148 specimens (80 specimens tested at ambient temperature and 68 specimens tested at high temperatures) were, fabricated, and tested under double-lap shear. Parameters investigated at ambient temperature comprised: (a) the bond length; (b) the number of layers; (c) the concrete surface preparation; (d) the concrete compressive strength; (e) the textile surface condition; and (f) the anchorage through wrapping with TRM jackets. Whereas, the parameters examined at high temperatures included: (a) the strengthening systems (TRM versus FRP); (b) the level of temperature at which the specimens were exposed; (c) the number of FRP/TRM layers; and (d) the loading conditions. The results of ambient temperature tests indicated that the bond at the TRM-concrete interface is sensitive to parameters such as: the number of layers, the textile surface condition, and the anchorage through wrapping with TRM. On the other hand, the results of high temperature tests showed that TRM exhibited excellent bond performance with concrete (up to 400 0C) contrary to FRP which practically lost its bond with concrete at temperatures above the glass trainset temperature (Tg). The flexural strengthening of RC beams with TRM at ambient and for the first time at high temperature was also examined carrying out 32 half-scale beams. The examined parameters were: (a) the strengthening system (TRM versus FRP); (b) the number of layers; (c) the textile surface condition; (d) the textile fibre material; (e) the end-anchorage system of the external reinforcement; and (f) the textile geometry. The results of ambient temperature tests showed that TRM was effective in increasing the flexural capacity of RC beams but its effectiveness was sensitive to the number of layers. Furthermore, a simple formula used for predicting the mean FRP debonding stress was modified for predicting the TRM debonding stress based on the experiment data available. The results of high temperature tests showed that TRM maintained an average effectiveness of 55%, of its effectiveness at ambient temperature, contrary to FRP which has totally lost its effectiveness when subjected to high temperature. Finally, a stress reduction factor of TRM flexural effectiveness (compared to its ambient effectiveness) when subjected to high temperature was also proposed.